Analisis Pembiayaan Murabahah pada Anggota KSPPS Karisma Kantor Cabang Grabag - Umi Hidayati; Chaidir Iswanaji; Ari Nurul Fatimah (Eksos, 2022)
Murabahah financing is a sale and purchase agreement of goods at a price higher than the agreed cost between the seller and the buyer. The murabahah contract is very much in demand by the public, especially financing trading activities and managing the business activities of members. This search aims to find out how murabahah financing is carried out by KSPPS KARISMA Grabag Branch Office. This study discusses the implementation of murabahah contracts, procedures and implementation of murabahah contracts for members at KSPPS KARISMA Grabag Branch Office, as well as the suitability of the application of murabahah contracts with sharia principles. This research method is descriptive qualitative, by conducting interviews, observations and by collecting primary data and secondary data. The results of the study that have been carried out by the author show that the analysis of the financing of the murabahah contract is in line with the principles syariah. There is evidence that the financing did not find anything contrary to Islamic teachings. For example, terms that contain elements of maisyir, gharar, haram, and usury.